2018
DOI: 10.1139/facets-2017-0106
|View full text |Cite
|
Sign up to set email alerts
|

Towards linking environmental law and science

Abstract: Gaps between environmental science and environmental law may undermine sound environmental decision-making. We link perspectives and insights from science and law to highlight opportunities and challenges at the environmental science-law interface. The objectives of this paper are to assist scientists who wish to conduct and communicate science that informs environmental statutes, regulations, and associated operational policies (OPs), and to ensure the environmental lawyers (and others) working to ensure that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Specifically, they identify the importance of producing time-critical research, attacking "wicked" problems, using multidisciplinary approaches, and better communicating their findings. Moore et al (2018) brought together environmental scientists and environmental lawyers to understand gaps, barriers, and opportunities to collaboration in the science-law interface and to develop a conceptual model of how different scientific activities can lead to more informed legislative, regulatory, and policy decisions. More recently, Fisher et al (2019) identified four practical steps intended to enhance the impact of environmental science on decision-making: (1) identify and understand your audience (or partners); (2) clarify the need for evidence; (3) gather "just enough" evidence; and (4) share and discuss the evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they identify the importance of producing time-critical research, attacking "wicked" problems, using multidisciplinary approaches, and better communicating their findings. Moore et al (2018) brought together environmental scientists and environmental lawyers to understand gaps, barriers, and opportunities to collaboration in the science-law interface and to develop a conceptual model of how different scientific activities can lead to more informed legislative, regulatory, and policy decisions. More recently, Fisher et al (2019) identified four practical steps intended to enhance the impact of environmental science on decision-making: (1) identify and understand your audience (or partners); (2) clarify the need for evidence; (3) gather "just enough" evidence; and (4) share and discuss the evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Applied ecologists are increasingly being called on to support evidence-based environmental and natural resource management [30]. The evidence we provide, therefore, must be based on sound empirical design, statistical analyses, and interpretations of these analyses [5].…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to align scientific evidence with the environmental laws and policies that regulate development of salmon estuaries (Moore et al, ). Specifically, our study, which represents the most comprehensive synthesis to date, indicates that the continued development of estuaries poses risks to salmon which is a factor to consider in decision‐making processes.…”
Section: Towards Informing Estuary Management For Salmonmentioning
confidence: 99%